Heroes of the Great Conflict; Life and Services of William Farrar : Smith, Major General, United States Volunteer in the Civil War - Wilson, James Harrison, 1837-1925 (Salt Lake City, UT : Project Gutenberg, 2004)
"Heroes of the Great Conflict; Life and Services of William Farrar Smith, Major General, United States Volunteer in the Civil War" by Wilson is a historical account written in the early 20th century. The book centers around the life and military career of Major General William Farrar Smith, detailing his significant contributions during the American Civil War and the challenges he faced within the military hierarchy. The opening of the book introduces William Farrar Smith, charting his early life, education at West Point, and his rise through the military ranks. It highlights his friendships with prominent Civil War figures and sets the stage for the examination of his military career during the war. The author emphasizes the importance of personal accounts and documentation, suggesting that a more nuanced understanding of Smith$1 (Bs character, motivations, and the complexities of military command is crucial, as opposed to relying solely on official reports. Through this lens, the narrative aims to shed light on not only Smith$1 (Bs achievements but also the political intricacies and interpersonal dynamics that affected his career trajectory. (This is an automatically generated summary.)s
Release date is 2004-12-23
E-text prepared by Nick Riles, Kat Jeter, Keith M. Eckrich, and the Project Gutenberg Online Distributing Proofreading Team
Keywords: United States -- History -- Civil War, 1861-1865 -- Biography; Smith, William Farrar, 1824-1903